Hyperglicemia in Childhood Acute Lymphoblastic Leukemia During Induction Chemotherapy - Nengcy Erlina Tasik Rerung1, Andi Cahyadi2 , Nur Rochmah3 , Maria Christina Shanty Larasati4, Mia Ra (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Hyperglycemia is a recognized side effect of the corticosteroids and asparaginase givenduring induction chemotherapy for pediatric acute lymphoblastic leukemia (ALL). The ALL is the malignanttumor with the highest incidence in the childhood. The aim of this study is to investigate the impact ofhyperglycemia during induction chemoteraphy in childhood ALL.Methods: This prospective study was done in Dr. Soetomo hospital from January to April 2018. The subjectwas newly diagnosed as ALL under the age of 18 years, treated with Indonesian childhood ALL 2013protocol (Standard Risk (SR) group and High Risk (HR) group). Hyperglycemia was defined as at leasttwo separate random plasma glucose levels > 200 mg/dL, which was evaluated before and during inductionchemotherapy. Statistical analysis using Paired T-test for parametric and Wilcoxon Test for nonparametric.Results: Thirty-three children were enrolled, 18/33 boys with mean age 5.8 (SD 3.78) years, compromisedas ALL-L1 30/33. They were treated with ALL-HR 19/33 and ALL-SR 14/33. In overall groups, the meanrandom blood glucose level significantly increased from 108 (SD 21.3) mg/dL to 147 (SD 48.1) mg/dL,(mean difference 38.67 mg/dL; 95% CI 18.08 to 59.26 mg/dL, P=0.008). In SR group, there was a significantincreased of mean random blood glucose level from 102 (SD 13.5) mg/dL to 133 (SD 37.3) mg/dL, (meandifference 31.8 mg/dL; 95% CI 8.78 to 54.8 mg/dL; P=0.01). In HR group, the mean random blood glucoselevel increased from 113 (SD 51.9) mg/dL to 165 (SD 25.4) mg/dL, (mean difference 51.9 mg/dL; 95% CI18.6 to 85.2 mg/dL, P=0.004).Conclusion: Blood glucose level is significantly increase during induction chemotherapy in both SR and HR Indonesian childhood ALL 2013 protocol.